2020
DOI: 10.1016/j.aquatox.2020.105485
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, fast and inexpensive bioassay to monitor benthic microalgae toxicity: Application to Ostreopsis species

Abstract: Even though HPLC-MS is commonly used to quantify the toxin content of Ostreopsis spp. cells, there is a need to develop easy-to-use toxicological tests to set thresholds during Ostreopsis spp. blooms. The crustacean Artemia has been widely used to evaluate the presence and toxicity of chemicals and biological contaminants and we anticipated that it could also be useful to test Ostreopsis spp. toxicity. Its relevance was first assessed by investigating the variability of the toxic effects among Ostreopsis spp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 75 publications
(91 reference statements)
1
7
0
Order By: Relevance
“…These toxin contents on a per-cell basis were higher than the values reported for other Mediterranean O. cf. ovata strains (7.5 to 75 pg tox cell −1 ) [ 4 , 58 , 70 , 71 ] and quite similar to those found for a French Mediterranean strain (up to 300 pg tox cell −1 ) [ 18 ] and the NW Mediterranean strain studied in García-Altares et al (2015) (up to 250 pg tox cell −1 ) [ 72 ]. Furthermore, it should be noted that the NW O. cf.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These toxin contents on a per-cell basis were higher than the values reported for other Mediterranean O. cf. ovata strains (7.5 to 75 pg tox cell −1 ) [ 4 , 58 , 70 , 71 ] and quite similar to those found for a French Mediterranean strain (up to 300 pg tox cell −1 ) [ 18 ] and the NW Mediterranean strain studied in García-Altares et al (2015) (up to 250 pg tox cell −1 ) [ 72 ]. Furthermore, it should be noted that the NW O. cf.…”
Section: Discussionsupporting
confidence: 76%
“…Impacts on marine fauna associated with Ostreopsis spp. blooms have been documented [ 2 , 3 ], and ecotoxicology studies are underway to elucidate the essential noxious mechanisms involved [ 4 , 5 ]. Palytoxin (PLTX) analogues (namely, putative or isobaric PLTX (isoPLTX) and ovatoxins (OVTXs)) synthesized by Ostreopsis species have been associated with sporadic but dramatic seafood-borne poisonings in the tropics [ 6 , 7 , 8 ] and, most commonly, with cutaneous and respiratory irritations in users of temperate beaches [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…ovata's growth or physiology, bidirectional effects may also be considered since some macroalgae have been shown to rely on microbial metabolites for cell division and differentiation (Wichard and Beemelmanns, 2018). The bioactive metabolites produced by the benthic dinoflagellate (Pavaux et al, 2020) may be detrimental or beneficial to the macroalgal host.…”
Section: Discussionmentioning
confidence: 99%
“…exposed to toxins produced by Ostreopsis sp. are not specific since our studies (Pavaux et al, 2020). The Artemia bioassay can be a prescreening test of Ostreopsis strains toxicity for OVTX analogues and other toxic metabolites produced by these dinoflagellates.…”
Section: Harmonization Of Ostreopsis Studies Including Ecotoxic Bio-amentioning
confidence: 95%
“…The Artemia bioassay can be a prescreening test of Ostreopsis strains toxicity for OVTX analogues and other toxic metabolites produced by these dinoflagellates. Indeed, the production of other toxic compounds that do not belong to the OVTX family was suggested by Ternon et al (2018) and confirmed by Pavaux et al (2020) because toxicity on Artemia was caused by Ostreopsis cf. ovata's fractions free of OVTXs.…”
Section: Harmonization Of Ostreopsis Studies Including Ecotoxic Bio-amentioning
confidence: 99%